Local hydrodynamic parameters of bubble column reactors operating with non‐Newtonian liquids: Experiments and models development. Issue 4 (28th December 2015) - Esmaeili, Amin; Guy, Christophe; Chaouki, Jamal
Abstract : The effects of liquid phase rheology on the local hydrodynamics of bubble column reactors operating with non‐Newtonian liquids are investigated. Local bubble properties, including bubble frequency, bubble chord length, and bubble rise velocity, are measured by placing two in‐house made optical fiber probes at various locations within a bubble column reactor operating with different non‐Newtonian liquids. It was found that the presence of elasticity can noticeably increase the bubble frequency but decreases the bubble chord length and its rise velocity. The radial profiles of bubble frequency, bubble chord length, and bubble rise velocity are shown to be relatively flat at low superficial gas velocity while they become parabolic at high superficial gas velocity. Moreover, the bubble size and gas holdup are correlated with respect to dimensionless groups by considering the ratio between dynamic moduli of viscoelastic liquids. The novel proposed correlations are capable of predicting the experimental data of bubble size and gas holdup within a mean absolute percentage error of 9.3% and 10%, respectively. © 2015 American Institute of Chemical Engineers AIChE J, 62: 1382–1396, 2016